Considerable variations in growth hormone policy and prescription in paediatric end-stage renal disease across European countries: a report from the ESPN/ERA-EDTA registry - Huis, Maike van; Schaefer, Franz (Nephrology, dialysis, transplantation, 2016)
AbstractBackground. Growth retardation in paediatric end-stage renal disease (ESRD) has a serious impact on adult life. It is potentially treatable with recomb
Advance Access publication 28 April 2015
Gesehen am 21.11.2019